Competition in the insurance sector: An application of Boone indicator - Sanderson Abel; Juniours Marire (Cogent Economics & Finance, 2021)
Competition in the insurance sector is an important element since it leads to the reduction in risk and uncertainty, enables efficient resources allocation, enhances product innovation, enhances economic growth and improves efficient production of financial services. The study evaluates competition in the insurance sector in Zimbabwe during the period 2010-2017. Of interest is the evolution of competition during the period when the economy had transitioned from hyperinflation. How competition evolved during this period is of interest due to the changes in macroeconomic management styles that were experienced after the hyperinflation period. Of novelty to this study is the use of the Boone Indicator, one of the new empirical industrial organisation methods. The method is premised on the idea that efficient firms achieve higher market shares or profits. The study established that competition was moderate in the insurance industry during the study period. The results further revealed that there was no significant difference in competition in the periods 2013-2017 and 2010-2012. The study recommends that the government should ensure that the macroeconomic environment is conducive for businesses to compete. The economy should be prevented from sliding into hyperinflationary environment, which negatively impacts policy holders as well as insurance companies. The government should put in place pro-growth policies to ensure insurance companies thrive. It has been shown that since the economy started experiencing moderate growth rates, there has been increased activity among insurance companies.
Keywords: 330; Boone; Competition; Efficient; Hyperinflation; Insurance